2021
DOI: 10.1097/md.0000000000027042
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of recto-sigmoid colon vaginoplasty using a three-dimensional laparoscopic technique

Abstract: To investigate the feasibility, safety, and outcomes of three-dimensional (3D) laparoscopic vaginoplasty with a rectosigmoid colon flap for vaginal reconstruction. Following appropriate preoperative patient counseling, 17 consecutive patients underwent vaginoplasty using a 3D laparoscopic system. Perioperative and postoperative outcomes were retrospectively evaluated. Between September 2016 and February 2020, 17 patients underwent 3D laparoscopic vaginoplasty with a rectosigmoid colon fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Although PIV remains the most commonly used approach, robotic peritoneal and intestinal techniques have demonstrated promising outcomes while offering the advantage of tissue capable of mucosal secretion, which has been suggested to facilitate wound healing and sexual intercourse without postoperative shrinkage. 43 These 2 techniques may thus be of particular advantage within patients with obesity to optimize wound healing and functional outcomes, as reflected by our results. In addition, the robotic approach allows for more precise tissue manipulation, minimized tissue damage, and enhanced visualization.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although PIV remains the most commonly used approach, robotic peritoneal and intestinal techniques have demonstrated promising outcomes while offering the advantage of tissue capable of mucosal secretion, which has been suggested to facilitate wound healing and sexual intercourse without postoperative shrinkage. 43 These 2 techniques may thus be of particular advantage within patients with obesity to optimize wound healing and functional outcomes, as reflected by our results. In addition, the robotic approach allows for more precise tissue manipulation, minimized tissue damage, and enhanced visualization.…”
Section: Discussionmentioning
confidence: 55%
“…Our multiple logistic regression model revealed that receipt of robotic peritoneal or robotic intestinal vaginoplasty procedures was associated with lower odds of developing delayed wound healing ( P < 0.001 and P = 0.011, respectively) across the study population. Although PIV remains the most commonly used approach, robotic peritoneal and intestinal techniques have demonstrated promising outcomes while offering the advantage of tissue capable of mucosal secretion, which has been suggested to facilitate wound healing and sexual intercourse without postoperative shrinkage 43 . These 2 techniques may thus be of particular advantage within patients with obesity to optimize wound healing and functional outcomes, as reflected by our results.…”
Section: Discussionmentioning
confidence: 58%
“…An outstanding advantage of laparoscopic surgery is that the establishment of carbon dioxide pneumoperitoneum can make the connective tissue space appear clearly and make it possible to identify the correct dissection layer[ 22 ]. In addition, 3D laparoscopy can overcome the disadvantages of traditional laparoscopy, such as lack of sense of space and distance, presenting a stereoscopic vision closer to open surgery[ 23 ]. However, compared with open surgery, the enlarged surgical field of 3D laparoscopy shows the anatomical structure more clearly, which is more conducive to delicate operations, making it easier to find the correct anatomical level, resulting in less surgical bleeding and adverse consequences.…”
Section: Discussionmentioning
confidence: 99%